Reader's Digest Natural Wonders of The World - Richard L. Scheffel; Susan J. Wernert (USA Reader's Digest Association, 1980)
The alphabetical format takes the reader from the depths of Switzerland's Aar Gorge to the craggy summit of the Zugspitze, high in the Bavarian Alps.
"Based on the book first published in France as Dictionnaire illustré des merveilles naturelles du monde."
Includes index.
Keywords: History, Geography and Archaeology; Natural monuments -- Dictionaries; Natural monuments -- General -- Encyclopedias